Groundwater vulnerability GIS models in the Carpathian mountains under climate and land cover changes - Nistor, Margarit Mircea (2019)
Water resources are facing nowadays with two main problems: climate change and land cover variation. Their influences on environment and water resources have been evidenced worldwide. In this work, we have applied a complex methodology based on Geographical Information System (GIS) to combine the spatial information of several parameters that allow to obtain the groundwater vulnerability under climate and land cover modifications. The spatial analysis performed in this paper includes the aquifers, water availability, load pollution index, and infiltration map raster grids data of Carpathian Mountains area, from Central Europe. The analysis presented in this study follow three periods, which include 30 years climate data models of 1961-1990 (1990s), 2011-2040 (2020s), and 2041-2070 (2050s). Land cover projections forecast future changes in artificial areas, agriculture areas, and forest areas for 2020s and 2050s. For both periods (2020s and 2050s), the very low vulnerability class area is reduced while the high class appears on a large area. The worst scenario is forecasted for 2050s (high vulnerability class increase up to 2.41% of the whole study area) and is mainly due to agriculture. These findings evidence the negative impact of land cover and climate changes on the groundwater resources in the Carpathians Mountains area. The original maps carried out in this work together with the concise methodology integrated in GIS may be a useful tool for the water resources management and future strategies plans of this region.